KOMITMEN ORGANISASI PADA GURU SD NEGERI UPTD PENDIDIKAN WIRADESA KABUPATEN PEKALONGAN - Karniti -; tukijan - (LPPM STIE DHARMAPUTRA SEMARANG, 2013)
The aim this research analyzes work motivation influence and organization culture towards organization commitment with job satisfaction as intervening variable. Population entire teachers at state elementryschool upt official education wiradesa pekalongan as much as 174 person and sample that taken as much as 154 person with use purposive sampling. Analyzer that used in this research path analysis. Hypothesis testing result shows that work motivation influence towards job satisfaction, influential organization culture towards job satisfaction, positive influential job satisfaction towards performance teacher, positive influential work motivation towards organization commitment. Path analysis result shows that work motivation positive influential towards organization commitment with job satisfaction as intervening variable, Organization culture positive towards organization commitment with job satisfaction as intervening variable Keyword: work motivation, organization culture, work satisfaction, organization commitment